2006
DOI: 10.1002/ajh.20710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood cyclosporine concentration on the outcome of hematopoietic stem cell transplantation from an HLA-matched sibling donor

Abstract: We retrospectively evaluated the effect of the blood cyclosporine (CsA) concentration on the outcome of allogeneic hematopoietic stem cell transplantation from an HLA-matched sibling donor in 171 patients who received a continuous infusion of CsA and short-course methotrexate to prevent graft-versus-host disease (GVHD). CsA was started at 3.0 mg/kg/day and the dose was adjusted to maintain the blood CsA concentration between 250 and 350 ng/ml. The actual dose of CsA averaged 1.9 mg/kg/day at the 3rd week after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 9 publications
(10 reference statements)
2
39
1
Order By: Relevance
“…However, the dose, target blood level, and schedule of administration vary among protocols and have not been optimized. 1 It has been shown that the blood concentration of CsA affects the incidences of acute GVHD and adverse events, 2 and an increase in the target blood concentration from 300 to 500 ng/ml in the continuous infusion of CsA significantly decreased the incidence of acute GVHD. 3 On the basis of these results, we are currently administering CsA by continuous infusion with target concentrations of 500 ng/ml for standard-risk patients and 300 ng/ml in highrisk patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dose, target blood level, and schedule of administration vary among protocols and have not been optimized. 1 It has been shown that the blood concentration of CsA affects the incidences of acute GVHD and adverse events, 2 and an increase in the target blood concentration from 300 to 500 ng/ml in the continuous infusion of CsA significantly decreased the incidence of acute GVHD. 3 On the basis of these results, we are currently administering CsA by continuous infusion with target concentrations of 500 ng/ml for standard-risk patients and 300 ng/ml in highrisk patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the posaconazole prescribing information also includes a recommendation for upfront reduction of the dose of CsA upon initiation of combined treatment (17), which emerged from a very small study of cardiac transplantation (16) and has never been analyzed in allo-BMT recipients. In these patients, the potential occurrence of subtherapeutic blood CsA levels, even transiently, has a strong negative impact on GVHD and on the outcome of allo- BMT (5,6,11,12,14,19). The clinical need for such an upfront CsA dose reduction in patients starting posaconazole in this clinical setting ought to be studied.…”
mentioning
confidence: 99%
“…Unfortunately, levels were assessed only twice, at the baseline and 2 weeks from the start of combined treatment, and neither earlier time points nor the need for upfront dose adjustment was analyzed. From 1988, when Yee et al first reported a significant association between low trough CsA concentrations and the risk of developing acute GVHD the following week (19), it is well established that subtherapeutic CsA levels after allo-BMT have a negative impact on transplant outcome (5,6,11,12,14). In order to avoid such subtherapeutic CsA levels, even transiently, general practice developed to widely accept that in the absence of toxicity, high blood CsA levels up to twice the upper limit of the therapeutic range would not require a dose reduction (1).…”
mentioning
confidence: 99%
“…Several cyclosporine administration protocols, including continuous infusion and higher target trough concentrations, are used. [13][14][15] Our method was considered a GVHD prophylaxis with a standard cyclosporine administration protocol during the time period included in this study;…”
Section: Multivariate Analysis Of Cumulative Gvhd Incidencementioning
confidence: 99%